Development of multifunctional unmanned aerial vehicles versus ground seeding and outplanting: What is more effective for improving the growth and quality of rice culture? - Qi, Peng; Wang, Zhichong; Wang, Changling; Xu, Lin; Jia, Xiaoming; Zhang, Yang; Wang, Shubo; Han, Leng; Li, Tian; Chen, Bo; Li, Chunyu; Mei, Changjun; et al. (Frontiers in Plant Science, 2022)
The mechanization efficiency is low in seeding, fertilization and pesticide application, which is labor-intensive and time-consuming. Currently, many researches focus on single operation of UAVs on rice, but there is a paucity of comprehensive application for the whole process of seeding, fertilization and pesticide application. Based on the previous research synthetically, a multifunctional unmanned aerial vehicle (mUAV) was designed for rice planting management based on the intelligent operation platform, which realized three functions of seeding, fertilizer spreading, pesticide application on the same flight platform. Computational fluid dynamics (CFD) simulations were used for machine design. And field trials were used to measure operating parameters. Finally, we conducted a comparative experimental analysis of the whole process by comparing the cultivation patterns of UMUAV seeding(T1) with mechanical rice direct seeder (T2) and mechanical rice transplanter (T3). The results showed that the downwash wind field of the MUAV fluctuated widely from 0-1.5 m, with the spreading height 2.5 m and the pesticide application height 3 m, which meet the operational requirements. There was no significant difference in yield between T1 and T2 and T3 test areas, while the differences in operational efficiency and input labor costs were large. In the sowing stage, T1 had obvious advantages, which the working efficiency was 2.2 times higher than T2 and the labor cost was reduced by 68.5%. The advantages were more obvious compared to T3, the working efficiency was 4 times higher than T3 and the labor cost was reduced by 82.5%. During the pesticide application, T1 still had an advantage, but it was not a significant increase in advantage relative to the seeding stage, which operating efficiency increased by 1.3 times and labor costs were reduced by 25%. However, fertilization of T1 was not advantageous due to load and other limitations. Compared to T2 and T3, which operational efficiency was reduced by 80% and labor costs increased by 14.3%. It is hope that this research will provide a new equipment for rice cultivation patterns in different environments, while improving rice mechanization, reducing labor inputs, and lowering costs.